Assessment of possible leakage effects of implementing EU COM proposals for the EU Biodiversity Strategy on forestry and forests in non-EU countries - Matthias Dieter; Holger Weimar; Susanne Iost; Hermann Englert; Richard Fischer; Sven Günter; Christian Morland; Hans-Walter Roering; Franziska Schier; Björn Seintsch; Jörg Schweinle; Eliza Zhunusova (Johann Heinrich von Thünen-Institut, 2020)
Overarching objective of the EU biodiversity strategy for 2030 is recovering biodiversity by strengthening the protection and restoration of nature. Key elements are the creation of protected areas on at least 30% of Europe's land and sea area, including stronger protective measures for forests. However, any implementation of dedicated measures will reduce roundwood production in EU member states. It is to be expected that parts of this reduced roundwood production will be compensated by increasing roundwood production in non-EU countries. There is a fundamental risk of biodiversity losses in non-EU countries accompanying such leakage of roundwood production. From a global perspective, such biodiversity losses must be opposed to biodiversity gains in EU countries. The presented study provides a first assessment of possible leakage effects and rep-resents the state of work as of September 2020. At first, the presented study provides an estimate of the decline in roundwood production in EU member states as a result of implementing partial or full production restrictions in forests. In a second step, implications of reduced roundwood production within EU-27 on global wood markets are assessed. Finally, leakage of roundwood production to non-EU countries is evaluated using indicators related to governance, sustainable forest management, biodiversity, forest condition, deforestation pressure and socio-economic aspects. In order to estimate the reduction in roundwood production in EU countries firstly three single implementation measures are assessed and then consolidated for Germany: (i) 10 % share of forest area set-aside, (ii) non-utilization of 'old-growth forests' and (iii) 30 % share of protected forest areas under Habitats Directive management requirements. As a result, the potential roundwood production in Germany declines on average within the period examined (2018 - 2052) by 23.96 million m³/a to 52.77 million m³/a or to 69 %. In the following calculations, this reduction share is assigned to all EU-27 countries. [...] – – Übergeordnetes Ziel der Biodiversitätsstrategie für 2030 der EU ist die Erholung der biologischen Vielfalt durch Verstärkung des Schutzes und der Wiederherstellung der Natur. Schlüsselelemente zur Erreichung der Ziele sind u.a. die Schaffung von Schutzzonen auf mindestens 30 % der Land- und Meeresgebiete und ein strengerer Schutz der europäischen Wälder. Die Implementierung konkreter Maßnahmen im Wald wird sich unmittelbar auf die Rohholzproduktion in den EU-Mitgliedsstaaten auswirken. Es ist jedoch zu erwarten, dass mindestens ein Teil der Rohholzproduktion in sogenannte Drittstaaten verlagert wird. Mit solchen Verlagerungseffekten besteht ganz grundsätzlich die Gefahr des Verlustes von Biodiversität in den betreffenden Drittstaaten. Aus einer globalen Perspektive müssen diese Biodiversitätsverluste dem Biodiversitätsgewinn in der EU gegenübergestellt werden. Die vorliegende Studie schätzt zunächst den Rückgang der Rohholzproduktion in den EU-Mitgliedsländern als Folge von vollständigen oder teilweisen Nutzungseinschränkungen in den Wäldern ab. Darauf aufbauend wird untersucht, wie sich eine reduzierte Rohholzproduktion innerhalb der EU-27 auf die globalen Holzmärkte auswirkt. Im dritten Schritt wird beurteilt, wie die Verlagerung der Rohholzproduktion in andere Länder anhand von Indikatoren zu Governance, nachhaltiger Waldbewirtschaftung, biologischer Vielfalt, Waldzustand, Entwaldungsdruck und sozio-ökonomischen Aspekten beurteilt werden kann. Für die Abschätzung des Einschlagsrückgangs werden drei verschiedene Umsetzungsmaßnahmen anhand verfügbarer Modellergebnisse für Deutschland untersucht und miteinander verschnitten: (i) 10 % Flächenanteil von Stilllegungsflächen im Wald, (ii) Verzicht auf die Holznutzung auf allen Standorten mit 'old-growth forest' und (iii) 30 % Anteil der verbleibenden Flächen mit naturschutzfachlichen FFH-Bewirtschaftungsauflagen. Das Ergebnis zeigt, dass unter diesem Szenario das potenzielle Rohholzaufkommen in Deutschland im Mittel für den Betrachtungszeitraum 2018 bis 2052 um insgesamt 23,96 Mio. m³/a auf 52,77 Mio. m³/a bzw. auf 69 % reduziert würde. Diese prozentuale Reduktion wird für die folgenden Berechnungsschritte auf alle EU-27-Länder übertragen. [...]
urn:nbn:de:gbv:253-202011-dn062850-7
Keywords: 630; leakage; biodiversity; EU; forestry; forests